Whole exome sequencing identifies LRP1 as a pathogenic gene in autosomal recessive keratosis pilaris atrophicans. Issue 9 (3rd July 2015) - Klar, Joakim; Schuster, Jens; Khan, Tahir Naeem; Jameel, Muhammad; Mäbert, Katrin; Forsberg, Lars; Baig, Shehla Anjum; Baig, Shahid Mahmood; Dahl, Niklas
Abstract : Background: Keratosis pilaris atrophicans (KPA) is a group of rare genodermatoses characterised by perifollicular keratosis and inflammation that progresses to atrophy and scars of the facial skin. Keratosis pilaris of extensor areas of limbs is a common associated finding. Most cases with KPA are sporadic and no consistent inheritance pattern has been documented. Methods: A large consanguineous Pakistani pedigree segregating autosomal recessive KPA of a mixed type was subject to autozygosity mapping and whole exome sequencing. Quantification of mRNA and protein levels was performed on fibroblasts from affected individuals. Cellular uptake of the low-density lipoprotein (LDL) receptor-related protein 1 (LRP1) ligand α2 -macroglobulin (α2 M) was quantified using fluorescence confocal microscopy. Results: Genetic analyses identified a unique homozygous missense variant (K1245R) in the LRP1 in all affected family members. LRP1 encodes the LRP1, a multifunctional cell surface receptor with endocytic functions that belongs to the LDL receptor family. The LRP1 mRNA and LRP1 protein levels in fibroblasts of affected individuals were markedly reduced when compared with controls. Similarly, the LRP1-mediated cellular uptake of α2 M was reduced in patient fibroblasts. Conclusions: This is the first report on LRP1 as a pathogenic gene for autosomal recessive KPA and keratosis pilaris. The inflammatory characteristics of the KPA entity in our family suggest a link to the immune-regulatory functions of LRP1.